Products Distribution from Suppliers to Retailers in Bandarlampung City (Case Study: Retailers location in Teluk Betung) - Salsabila, Annisa; Nikmah, Nadhir Rotun; Bakhtiananda, Rafif Syadid; Aswin, Micelle Yap; Nurvazly, Dina Eka (Magister Program of Mathematics, Universitas Lampung, 2024)
Traveling Salesman Problem(TSP) is a problem where a salesman visits cities, each city is connected, and there are weights to move between cities, thus forming a complete weighted graph. The objective of the TSP is to determine all city routes with the lowest total weight. Cheapest Insertion Heuristic (CIH), one of the algorithms to solve TSP. This algorithm provides different travel routes depending on the order of city elimination on the subtour in question. In this study, the CIH algorithm will be discussed to determine the shortest route for distribution of goods from suppliers to several retailers in the city of Bandarlampung, especially for 23 retailers whose locations in Teluk Betung sub-district. The result shows that the total distance travel from the supplier to the 23 retailers and then back to the supplier location is 34.84 km.